An alternative to motivate learners and to develop moral values in future physical and sports education professionals, using visual aids of USA-Cuba discrepancy in the teaching-learning process - Silvio Rizo-Valdés; Huberlán Miranda-Acosta; Rubén Posada-Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
This article deals with a pedagogical alternative to motivate learners in classes with reference to USA-Cuba discrepancy using visual aids that express the different actions and aggressions of US-imperialism to Latin America, specifically our country with the purpose of widening its military supremacy and the policy of annexation towards our Island. The classes involve two main moments: 1- a directed lecture, 2- a workshop session to conclude; achieving the objectives of this pedagogical alternative, to the development of a set of teaching and intellectual skills contributing this way to the enhancement of moral values such as: identity, patriotism, anti-imperialism and solidarity among others.